Glucose-coated superparamagnetic iron oxide nanoparticles prepared by metal vapor synthesis can target GLUT1 overexpressing tumors: In vitro tests and in vivo preliminary assessment. - Daniele Barbaro; Lorenzo Di Bari; Valentina Gandin; Cristina Marzano; Andrea Ciaramella; Michele Malventi; Claudio Evangelisti (PLoS ONE, 2022)
Superparamagnetic iron oxide nanoparticles (SPIONs) coated with glucose (Glc-SPIONs) were prepared by a new approach called Metal Vapor Synthesis (MVS) and their morphological/structural features were investigated by transmission electron microscopy (TEM) and dynamic light scattering. TEM analysis revealed the presence of small roundish crystalline iron oxide nanoparticles in the organic amorphous phase of glucose, The particles were distributed in a narrow range (1.5 nm-3.5 nm) with a mean diameter of 2.7 nm. The hydrodynamic mean diameter of the Glc-SPIONs, was 15.5 nm. From 4 mg/mL onwards, there was a constant level of positive contrast in a T1-weighted sequence. In vitro experiments were performed in three cell lines: pancreatic cancer (PSN-1), human thyroid cancer (BCPAP), and human embryonic kidney non-tumor cells. We evaluated GLUT1 expression in each cell line and demonstrated that the exposure time and concentration of the Glc-SPIONs we used did not affect cell viability. PSN-1 cells were the most effective at internalizing Glc-SPIONs. Although significantly higher than the control cells, a lower Fe content was detected BCPAP cells treated with Glc-SPIONs. To confirm the involvement of GLUT1 in Glc-SPIONs internalization, cellular uptake experiments were also conducted by pre-treating cancer cells with specific GLUT1 inhibitors, All the inhibitors reduced the cancer cell uptake of Glc-SPIONs In vivo tests were performed on mice inoculated with Lewis lung carcinoma. Mice were treated with a single i.v. injection of Glc-SPION and our results showed a great bioavailability to the malignant tissue by the i.v. administration of Glc-SPIONs. Glc-SPIONs were efficiently eliminated by the kidney. To the best of our knowledge, our study demonstrates for the first time that Glc-SPIONs prepared with MVS can be electively internalized by tumor cells both in vitro and in vivo by exploiting one of the most universal metabolic anomalies of cancer.